Code switch problem and language contacts - J N Ebzeeva (Russian journal of linguistics: Vestnik RUDN, 2012)
The article deals with the questions of the theory of language contacts, bilingualism and code switch. The authors analyze French lexical-semantic units used in English-speaking magazines as the reflection of the code switch process.